High Efficient of Ca/Al-Graphite for Removal of Direct Orange - Yusuf Mathiinul Hakim; Rananda Vinsiah; Shahibul Fajri (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
The layered double hydroxide-based material features of Ca/Al have improved according to the adsorption capacity and structure stabilization by transforming into composite Ca/Al-graphite. The composite was synthesized by co-precipitation method, and the chemical structure was characterized using X-ray Diffraction (XRD), Fourier Transform Infra-red (FT-IR), Brunauer Emmet-Teller (BET) Surface Area, and Thermo-Gravimetry Differential Analyse (TG-DTA). The XRD analysis of Ca/Al-Graphite composite was noticed in 10.205°(003), 18.083°(012), 20.45°(004), 26.532°(002), 44.52°(101), 54.52°(004), and 77.38°(006). The TG-DTA analysis of the composite was noticed at 100°C as water molecule decomposition, 270°C as nitrate decomposition, and 700 and 760°C as graphite decomposition to the oxide form. BET surface area analysis of Ca/Al-Graphite composite achieved the highest surface area at 16.795 m2/g. According to the kinetic parameter, the adsorption of direct orange to composite follows the pseudo-second-order model. The isotherm parameter of direct orange adsorption onto the composite followed the Langmuir model and occurred spontaneously and endothermically. The regeneration study proved the composite effective in 3 cycles by adsorption percentage at the third cycle reached 73.559%.